MADRASAH NIZHAMIYAH: SEBUAH MOMENTUM DALAM SEJARAH PENDIDIKAN ISLAM - Novianti Muspiroh (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2017)
Madrasah Nizhamiyya is the momentum of the history of Islamic education, the pioneer of institutional Islamic education system, and the driving force behind the establishment of similar institutions in the history of Islamic education. In addition, the birth of this educational institution is also seen as an effort to awaken Sunni orthodoxy. On the other hand, this institution is the starting point for the decline of science, because the supremacy of the religious sciences in it raises the dichotomy and antagonization of various branches of science. Whereas in Islam there is no recognition of the essential separation between the religious sciences and the "profane sciences", because it all boils down to the knowledge of the Only One - the substance of all knowledge.Keywords: Madrasah, education, Sunni